Pemanfaatan Fungi Mikoriza Arbuskula (Fma) Pada Pot Organik Untuk Meningkatkan Pertumbuhan Kayu Afrika (Maesopsis eminii Engl) di Persemaian Permanen Dramaga - Sri Wilarso Budi; Maryani Fatimah Putri Hardhani (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2020)
The increase cultivation of tree causes the great number of polybags used. To reduce the polybag, the organic pot based on the organic materials that is environmentally friendly is able to be implemented. This study aimed to analyze the effect of organic pot with the addition of Arbuscular Mycorrhizal Fungi (AMF) to develop the growth quality of Maesopsis eminii seedling. This study used the completely randomized design with two factors method. The results of this study showed that the interaction of organic pot treatment and the addition of Arbuscular Mycorrhizal Fungi were significantly affected on the height of Maesopsis eminii seedling. A single treatment of Arbuscular Mycorrhizal Fungi (AMF) addition was significantly affected on the root dry weight as well as the percentage of Arbuscular Mycorrhizal Fungi (AMF) colonization on the root of Maesopsis eminii seedling. The composition of organic pot of newspaper:rice husk with the addition of Arbuscular Mycorrhizal Fungi was the best treatment to enhance the growth of Maesopsis eminii seedling. Keywords: Arbuscular Mycorrhizal Fungi (AMF), kayu afrika (Maesopsis eminii Engl), Organic Pot